The Effect of Capital Structure, Profitability, Dividend Policy, Liquidity and Asset Structure on Stock Prices (Empirical Study on LQ45 Companies Listed on the Indonesia Stock Exchange in 2019-2023) - Nasywa Nathania Hirda; Setiawati, Erma (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of capital structure, profitability, dividend policy, asset structure, and liquidity on stock prices of LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. A quantitative approach was used, relying on secondary data obtained from the financial statements of selected companies through purposive sampling. The research sample consists of 18 companies, resulting in 89 observations after outlier adjustments. The data were analyzed using multiple linear regression, preceded by classical assumption tests. The results show that only capital structure has a significant effect on stock prices, while profitability, dividend policy, asset structure, and liquidity do not have a significant impact. The coefficient of determination (Adjusted R²) is 0.082, indicating that the independent variables in this model explain only 8.2% of the variation in stock prices, with the remaining 91.8% explained by other factors outside the model. This research is expected to contribute to the development of financial theory and serve as a reference for investment decision-making.